Application of the beam method to structural calculation of the long cylindrical concrete shells in the work of Felix Candela - Martínez Martínez, Mónica (Revista de la Construcción. Journal of Construction, 2019)
In the present work it is explained how the architect Felix Candela got to analyse the roof long cylindrical shells in reinforced concrete using an method based simply on equilibrium equations. All this, in a moment in which the elastic theory of shells becomes practically impossible to apply due to the involvement of eighth-order differential equations. Felix Candela ‘objective was to get a safely and easily calculation method, respecting the assignment of reinforced concrete and, therefore, obviating the considerations of compatibility and deformation that could undergo the structure. This method, developed previously by other engineers, is explained mathematically choosing an example of work of Félix Candela, done by roof long cylindrical shells, and making the necessary structural calculations proposed.